Toward Efficient Low Cost Highly Accurate Emotion Speech Synthesizer, - Mahmood, Ahmed Mustafa; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Hameed, Shihab A. (IJCSNS, 2008)
Abstract: A Text to Speech (TTS) system with the ability to express emotions is an interesting technology that is still under development. There have been multiple proposals to simulate emotion so far, and there are multiple dimensions for assessment. No system guarantees high score in all of these dimensions, this means that no system works in a direction to get low computation load, small database along with high accuracy and excellent voice quality. After all of these qualities are relative and fuzzy and there is no rigid grading system. In this paper we will propose a new path for research that will work toward improving all of the quality factors together, so that future work can come up with a more optimum solution for the emotional TTS systems.